2007
DOI: 10.1002/chem.200601791
|View full text |Cite
|
Sign up to set email alerts
|

Gold‐Catalyzed Cyanosilylation Reaction: Homogeneous and Heterogeneous Pathways

Abstract: Gold had been considered to be an extremely inert metal, but recently it was found that nanometer-sized gold particles on metal-oxide supports acted as catalysts for simple organic reactions, such as oxidation and hydrogenation, even at or below room temperature. Herein, we report that gold nanoparticles (AuNPs) of zero oxidation state (Au0) are catalytically active for a C--C bond-forming reaction, the cyanosilylation of aldehydes. The AuNP-catalyzed cyanosilylation proceeded smoothly at room temperature with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(11 citation statements)
references
References 73 publications
0
11
0
Order By: Relevance
“…Over the years, many catalysts have proved to be excellent for the cyanosilylation of aldehydes;n evertheless, when ketonesw ere used as substrates, only af ew heterogeneous catalysts have shown good conversions. [53][54][55][56][57][58][59][60][61][62][63][64] Previous studies with indium MOFs have concluded that these materials exhibit good catalytic activity in such reactions with low loadings,m ild temperatures, and without solvent. [14][15][16] The cyanosilylation reactions were performed by using low catalytic amounts (1-5 mol %), under an inert atmosphere, without solvent, and at room temperature.…”
Section: Catalytic Activity Of Inpf Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the years, many catalysts have proved to be excellent for the cyanosilylation of aldehydes;n evertheless, when ketonesw ere used as substrates, only af ew heterogeneous catalysts have shown good conversions. [53][54][55][56][57][58][59][60][61][62][63][64] Previous studies with indium MOFs have concluded that these materials exhibit good catalytic activity in such reactions with low loadings,m ild temperatures, and without solvent. [14][15][16] The cyanosilylation reactions were performed by using low catalytic amounts (1-5 mol %), under an inert atmosphere, without solvent, and at room temperature.…”
Section: Catalytic Activity Of Inpf Materialsmentioning
confidence: 99%
“…MW synthesis:A mixture of H 3 popha (0.030 g, 0.085 mmol) and In(OAc) 3 (0.033 g, 0.114 mmol) in water (2 mL) was placed in ag lass vial and submitted to MW radiation by using ad ynamic method at 170 8Cw ith vigorous stirring (30 min, 200 W, 10 bar), which led to formation of the product InPF-16 (0.265 g, 97 %). Elemental analysis calcd (%) for C 90 H 56 (air,f low rate = 100 mL min À1 ): initial weight loss (of % 5%)s tarted at 100 8C, which was due to the loss of coordinated and physisorbed water molecules;a t% 420 8Ca60 %l oss of material had occurred;t he final residue that remained at % 800 8Cc orresponded to 35 %o ft he material that was converted into In 2 O 3 (ICSD_ 640179).…”
Section: Preparation Of Inpf Materialsmentioning
confidence: 99%
“…Also, aromatic and aliphatic ketones, such as acetophenone or its 4-nitro derivative, 2-heptanone and cyclohexanone gave the corresponding cyanohydrins in high to quantitative yields. However, addition of TMSCN to ketones is slower in comparison with aldehydes due to more steric hindrance around the carbonyl group of ketones than of aldehydes (entries [16][17][18][19] [5,6].…”
Section: Resultsmentioning
confidence: 98%
“…Complete removing or replacement of a safer solvent in a chemical process is likely to often be the greatest reduction and simplification (in the work-up as well as the reaction) that can be achieved [52]. To the best of our knowledge, most of the introduced protocols for cyanosilylation of carbonyl compounds have been reported by using toxic solvents such as DMF [21,[43][44][45], CH 3 CN [1,12,[23][24][25], CHCl 3 [40] or CH 2 Cl 2 [11][12][13][14][15][16][17]19,26,[34][35][36][37][38][39]51] and the number of methods under solvent-free conditions remains quiet limited [5,6,18,33,49]. In continuation of our interest to develop new efficient nucleophilic organocatalysts for cyanosilylation of carbonyl compounds [33][34][35], we herein disclose the application of potassium phthalimide (PPI) as an efficient organocatalyst for the addition of TMSCN to carbonyl compounds under mild and solvent-free conditions affording various cyanohydrin trimethylsilyl ethers (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation